THE COMPARISON BETWEEN STAD +3R BASED ON DIGITAL MEDIA METHODS AND THE COOPERATIVE MODEL STAD TYPE IN WRITING EXPLANATION TEXT - Yudi Cahyadi; Wikanengsih Wikanengsih (JLER (Journal of Language Education Research), 2020)
The research was backed by Permendikbud number 37 the year 2018, students need to master the technology in writing, thus it takes the right learning method in line with the Permendikbud, researchers offer a method of innovative study that is the method of the STAD + 3R based digital media. The writing that corresponds to KI KD is one of the explanation text. The purpose of this research is to learn the students ' learning outcomes in writing the explanation text based on digital media and the different methods STAD +3R based digital media with STAD. The research methods used are quantitative comparatively with the quasi-experiments in the form of a Nonequivalent control group. The population in this study was 300 students of grade VIII SMP Negeri 3 Padalarang. Sampling uses purposive sampling and obtained class VIII B as an experimental class as many as 30 students and class VIII A as a control class as many as 30 students. The results showed an average increase in the value of 21.87 points or 28% from 56.13 to 78. The significant difference through the statistical test with a signification value of 2-tailed test T independent sample test is 0.03 < 0.05, it can be concluded there is a meaningful difference between the STAD class with the STAD +3R class, the student performance in the STAD +3R class generates digital products in the form of Vlog, Pptx and E-book, while the STAD class does not produce digital products. Keywords: explanation text, innovative methods, methods of STAD +3R based digital media.